Co-creating academic career self-efficacy: exploring academic career segments, mediating and moderating influences in engineering education trajectory - Mahajan, Prashant (Frontiers in Education, 2024)
Introduction This study explores the dynamic relationship among different academic career stages within engineering education, using academic career self-efficacy (ACSE) – one’s belief in their academic ability, as the unitary construct. The purpose of this study was to examine the relationships between the academic career segments demonstrating self-efficacy at the beginning of career, during academic progression, and post-graduation completion, along with the mediating and moderating effects corresponding to the relationships. Methods Quantitative survey was conducted on Indian recent engineering graduates. Data was collected from closed-ended questionnaire. Structural equation modeling was employed to analyze the relationships among academic career segments, mediation and the moderating impact of personal traits. Results There were statistical significances among the relationships between academic career segments with each other. Notably, ACSE during academic progression emerged as a crucial mediator between entry-level ACSE and ACSE post-graduation completion. Furthermore, gender, social caste, engineering major, campus placement and engineering grade were identified as significant moderators for these relationships. Discussion It sheds light on the significance of ACSE throughout diverse academic career segments enhancing career aspirations, engineering skills, and expressions and reflections that facilitate collaborative co-creation for engineering as a career. It contributes to the positive propagation of engineering education as an excellent and rewarding career choice.